Autonomic neurophysiologic implications of disorders comorbid with bladder pain syndrome vs myofascial pelvic pain. Issue 5 (4th April 2019) - Chelimsky, Gisela G.; Yang, Sheng; Sanses, Tatiana; Tatsuoka, Curtis; Buffington, C. A. Tony; Janata, Jeffrey; McCabe, Patrick; Dombroski, Mary‐Alice; Ialacci, Sarah; Hijaz, Adonis; Mahajan, Sangeeta; Zolnoun, Denniz; et al.
Abstract : Aims: The neuropathophysiology of a debilitating chronic urologic pain condition, bladder pain syndrome (BPS), remains unknown. Our recent data suggests withdrawal of cardiovagal modulation in subjects with BPS, in contrast to sympathetic nervous system dysfunction in another chronic pelvic pain syndrome, myofascial pelvic pain (MPP). We evaluated whether comorbid disorders differentially associated with BPS vs MPP shed additional light on these autonomic differences. Methods: We compared the presence and relative time of onset of 27 other medical conditions in women with BPS, MPP, both syndromes, and healthy subjects. Analysis included an adjustment for multiple comparisons. Results: Among 107 female subjects (BPS alone = 32; BPS with MPP = 36; MPP alone = 9; healthy controls = 30), comorbidities differentially associated with BPS included irritable bowel syndrome (IBS), dyspepsia, and chronic nausea, whereas those associated with MPP included migraine headache and dyspepsia, consistent with the distinct autonomic neurophysiologic signatures of the two disorders. PTSD (earliest), anxiety, depression, migraine headache, fibromyalgia, chronic fatigue, and IBS usually preceded BPS or MPP. PTSD and the presence of both pelvic pain disorders in the same subject correlated with significantly increased comorbid burden. Conclusions: Our study suggests a distinct pattern of comorbid conditions in women with BPS. These findings further support our hypothesis of primary vagal defect in BPS as compared with primary sympathetic defect in MPP, suggesting a new model for chronic these pelvic pain syndromes. Chronologically, PTSD, migraine, dysmenorrhea, and IBS occurred early, supporting a role for PTSD or its trigger in the pathophysiology of chronic pelvic pain.